Sensory and Nutrient Analysis of Watermelon Pilipit - Abaya, Desa D.; Barroga, Anna Marie D.; Divina, Francisco N.; Liberato, Milagros L.; Liberato, Zosimo O.; Chavez, Jennifer C. (Future Science / FSH-PH Publications, 2026)
This study was conducted to improve or develop food products and processing technologies, specifically those that will enhance value addition. The creation of new marketable forms from watermelon rind and skin is usually discarded. The study used an experimental design, employing a completely randomized design with four treatments, each replicated three times. Different measurements of watermelon rind and skin puree were used to represent the treatments of the study. The products were evaluated by 50 respondents composed of ten (10) trained faculty on sensory evaluation of products, 35 student evaluators who know food preparation and evaluation of products, and five (5) selected bakery owners from the Municipality of Sta. Maria Ilocos Sur. Results showed that 400ml of watermelon rind and skin puree, combined with basic ingredients, was best across all sensory evaluations and had the highest return on investment (ROI). Based on the study, the watermelon pilipit is considered healthy, acceptable, and nutritious. It contained ash of 1.12g, moisture content of 12.96g, crude fat of 11.0g, and 10.37g of crude protein. The technology should undergo further testing, including shelf-life and physicochemical tests. This study recommends using watermelon skin and rinds as an enhancer in making pastry products such as chips and pilipit